Iron-Catalysed Aerobic Oxidative C–C Bond Cleavage of Ketones for the Synthesis of Primary Amides - Zhan, Haosheng; Hu, Zhiwei; Tao, Weihua; Ling, Min; Cao, Wei; Lin, Jing; Liu, Zhenhua; Wang, Yu; Fang, Zhongxue (SynOpen, 2019)
An iron-catalysed aerobic oxidative C–C bond cleavage of ketones for the synthesis of primary amides has been developed using TEMPO and oxygen as an oxidant. This reaction tolerates a wide range of substrates, and primary amides are obtained in good to excellent yields. Substrates with long-chain alkyl substituents could also be selectively cleaved and converted into the corresponding amides.
Keywords: C–C bond cleavage; ketone; primary amide; amide; iron-catalysis